INFLUENCE OF DIVIDEND POLICY AND CAPITAL STRUCTURE ON FIRM VALUE - Ati Sumiati; Adhi Gunawan; Susi Indriani (Fakultas Ekonomi Universitas Negeri Jakarta, 2019)
The purpose of this research is to know the influence between dividend policy and capital structure on company value at the manufacturing company listed in BEI period 2016. The method in this research is a quantitative method with descriptive statistical analysis. The data analysis tool used is multiple linear regression. Sampling technique in this study using simple random sampling. The affordable population in this study were all manufacturing companies listed on the Indonesia Stock Exchange and the sample used on Isaac Michael's table was 44 companies. Test requirements analysis is done by looking for regression equation that yield Y = 1,367 + 0,163X1 + 12,236X2. The results of the analysis show: (i) there is a significant positive influence between dividend policy and firm value, (ii) there is a significant positive influence between capital structure and firm value, (iii) there is significant relation between dividend policy and capital structure to firm value. Based on the results of the analysis, the dividend policy and capital structure can be a measure of corporate value. The implication of this research explains that dividend policy and capital structure can be used as the basis of the investor's consideration before investing in a company.